TFIID is required for in vitro transcription of the human U6 gene by RNA polymerase III. - Simmen, K A (1991)
We present evidence that transcription factor TFIID, known for its central role in transcription by RNA polymerase II, is also involved in RNA polymerase III transcription of the human U6 snRNA gene. Recombinant human TFIID, expressed either via a vaccinia virus vector in HeLa cells or in Escherichia coli, affects U6 transcription in three different in vitro assays. First, TFIID-containing fractions stimulate U6 transcription in reactions containing rate-limiting amounts of HeLa nuclear extract. Second, TFIID addition relieves transcriptional exclusion between two competing U6 templates. Third, TFIID can replace one of two heat labile fractions essential for U6 transcription. Thus, at least one basal transcription factor is involved in transcription by two different RNA polymerases.